The Impact of Protective Measures for Female Workers - Zveglich, Jr., Joseph E.; van der Meulen Rodgers, Yana (Journal of Labor Economics, 2003)
Policies designed to protect female workers have controversial effects on labor market outcomes, both in theory and in practice. The analysis uses repeated cross‐sections of household survey data for Taiwan to estimate the impact of working‐hours restrictions and maternity benefits. Differential coverage across industrial sectors and demographic groups provides a unique opportunity to identify the impact of both policies in a single natural experiment framework. While working‐hours restrictions have a negative impact on women's actual hours worked and employment, maternity benefits increase these labor inputs, implying that women value the opportunity to return to jobs they might otherwise have to leave.